Combinatorics and finite fields : difference sets, polynomials, pseudorandomness and applications - Schmidt, Kai-Uwe; Winterhof, Arne (Radon series on computational and applied mathematics ;, 2019)
Combinatorics and finite fields are of great importance in modern applications such as in the analysis of algorithms, in information and communication theory, and in signal processing and coding theory. This book contains survey articles on topics such as difference sets, polynomials, and pseudorandomness.- Resumé vydavatel